First results from petrographic analyses on archaeological samples form the lower basin of the Colorado river (Buenos Aires province, Argentina) - Santos Valero, María Florencia; Martinez, Gustavo Adolfo; Frisicale, Maria Cristina (Consejo de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Historia y Ciencias Humanas, 2018)
The lower basin of the Colorado river is an ecotonal area located at the eastern Pampa-Patagonia transition (Figure 1). The archaeological record recovered in this area includes a great diversity of materials among which lithic artifacts are an important part. The analysis of these materials allows us to know the raw materials selected, their procurement methods, those chaînes opératoires involved in its knapping and the main characteristics of the artefactual assemblages (Armentano 2014; Santos Valero 2017). Among the different kinds of rocks exploited by the hunter-gatherers it was possible to recognize those that were coming from the study area, and other whose sources were localized in neighboring regions, among which are the Humid and Dry Pampa subregions and Northpatagonia. However these assignments were preliminary proposed on the basis of macroscopic characterization. Because of this the aim of this work is to present the results obtained from the petrographic cuts of archaeological artifacts coming from Middle and Late Holocene sites recorded at the lower basin of the Colorado river. These analyses were carried out in order to generate a more accurate knowledge of the provenience of the raw materials over which these artifacts were manufactured.